Intelligent Multimedia Communication: Techniques and Applications - Chen, Chang Wen.; Li, Zhu.; Lian, Shiguo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Multimedia data are used more and more widely in human being's life, e.g., videoconferencing, visual telephone, IPTV, etc. Nearly most of the applications need multimedia transmission techniques that send multimedia data from one side to another side and keep the properties of efficiency, robustness and security. Here, the efficiency denotes the time cost of transmission operations, the robustness denotes the ability to survive transmission errors or noises, and the security denotes the protection of the transmitted media content. Recently, various intelligent or innovative techniques are invented, which bring vast performance improvements to practical applications. For example, such content transmission techniques as p2p, sensor network and ad hoc network are constructed, which adaptively use the peers$1 (Bproperties to improve the network$1 (Bs resources. Multimedia adaptation techniques can adjust the multimedia data rate in order to compliant with the network$1 (Bs bandwidth. Scalable encryption techniques can generate the data stream that can be correctly decrypted after bit rate conversion. Ubiquitous multimedia services make the user share any kind of content anywhere. The book includes fourteen chapters highlighting current concepts, issues and emerging technologies. Distinguished scholars from many prominent research institutions around the world contribute to the book. The book covers various aspects, including not only some fundamental knowledge and the latest key techniques, but also typical applications and open issues. For example, the covered topics include the present and future video coding standards, stereo and multiview coding techniques, free-viewpoint TV techniques, wireless broadcasting techniques, media streaming techniques, wireless media transmission techniques and systems, and User-Generated Content sharing.s
Rate Control and Error Resilience for Object-based Video Coding -- Representation and Coding Formats for Stereo and Multiview Video -- Present and Future Video Coding Standards -- AVS Video Coding Standard -- A Resolution Adaptive Video Compression System -- Peer-to-Peer Streaming Systems -- Topology Construction and Resource Allocation in P2P Live Streaming -- Intelligent Video Network Engineering with Distributed Optimization: Two Case Studies -- Media coding for streaming in networks with source and path diversity -- Peer-assisted Media Streaming: a Holistic Review -- Free-Viewpoint TV (FTV) -- UGC Video Sharing: Measurement and Analysis -- Terrestrial Television Broadcasting in China: Technologies and Applications -- Network Topology Inference for Multimedia Streaming -- Resolution-Improvement Scheme for Wireless Video Transmission.
Keywords: Engineering; Information systems; Artificial intelligence; Engineering mathematics; Telecommunication; Engineering; Appl.Mathematics/Computational Methods of Engineering; Artificial Intelligence (incl. Robotics).; Communications Engineering, Networks; Information Systems and Communication Service